Attention Deficit Hyperactivity Disorder Handbook A Physician's Guide to ADHD - Millichap, J. Gordon; SpringerLink (Online service) (New York, NY : Springer New York : Imprint: Springer, 2011)
Readers of Attention Deficit Hyperactivity Disorder Handbook: A Physician's Guide to ADHD, second edition will find a concise and scholarly work covering the most recent advances in causes and management of ADHD. The book provides answers to the numerous questions that surround ADHD, such as: How is ADHD diagnosed? What causes ADHD? What are the risks of associated learning and behavior disorders, tics, seizures, and headaches? What treatments are available? What are the choices of medications and the risks of side effects? Do children outgrow ADHD? Author, J. Gordon Millichap, M.D., F.R.C.P., is a pediatric neurologist with more than 40 years experience in treating children, adolescents, and young adults with ADHD and related medical disorders (tics, Tourette syndrome, headache, seizures, learning disorders, dyslexia). Dr. Millichap has done research studies on medications and dietary therapies for ADHD, and advises on the pros and cons of medications vs. alternative therapies. He has experience with the long-term effects of medications, their side effects, and ways to minimize risks. Dr. Millichap is the Director of the Attention Deficit Disorder Clinic, Division of Neurology, at Children$1 (Bs Memorial Hospital, and Professor Emeritus at Northwestern University Medical School, Chicago, Illinois. His vast clinical and research experience coalesce in A Physician's Guide to ADHD, a comprehensive and clinically useful guide for any medical professional treating patients with ADHD.s
Definition Of ADHD -- Causative Factors -- Symptoms And Signs -- Diagnosis And Laboratory Tests -- Comorbid Disorders -- Learning And Language Disorders -- Tics, Seizures, And Headaches -- Methods Of Management -- Medications For ADHD -- Dietary And Alternative Therapies -- Prognosis And Prevention -- Management Roles.
Keywords: Medicine; Family medicine; Neurology; Pediatrics; Psychiatry; Medicine & Public Health; Neurology; Pediatrics; General Practice / Family Medicine; Psychiatry